The making of neoliberal Turkey - Özbay, Cenk; Erol, Maral; Terzio?lu, Ayşecan; Türem, Ziya Umut (Ashgate Publishing Ltd, 2016)
Exploring the divergent aspects of the rule of neoliberalism in Turkey since 1980s, each chapter in this book highlights a specific dimension of this socio-economic process and together, these essays construct a thorough examination of the whirlwind of changes recently experienced by Turkish society. With particular focus on the new ways in which social power operates, expert contributors explore new discourses and subjectivities around environmentalism, health, popular culture, economic policies, feminism and motherhood, urban space and minorities, class and masculinities. By questioning the primary influence of the state in these micro-political matters, they engage with concepts of neoliberalism and governmentality to provide a fresh, grounded and analytical perspective on the routes through which social power navigates the society. This sustained examination of the new axes of power and subjectivity, with a particular eye on the formation of new political spaces of governance and resistance, deepens the analysis of Turkey’s experiment with neoliberal globalization.
Keywords: Neoliberal Turkey; Making